A 5-gene DNA methylation signature is a promising prognostic biomarker for early-stage cervical cancer. (17th February 2022) - Chen, Hongxia; Li, Hongying; Wang, Lei; Li, Yaxiong; Yang, ChunYan
Abstract: The demographic information and overall survival (OS) of patients with cervical cancer (CC) (pathological stage: IA–IIA) were extracted from the TCGA database. A univariate and multivariate Cox proportional hazard model was performed to identify methylation markers significantly associated with the OS of patients in the training dataset. Then such a prognostic classifier was tested on the validation set and all subgroups. The Kaplan–Meier analysis and ROC analysis were performed to detect the ability to discriminate between patients with different risks and different OS. A DNA methylation signature which contained five genes was found to be significantly associated with the OS of CC patients by the Cox regression analysis in the training dataset. Such a signature could efficiently distinguish the patients into two risk groups with significantly different OS in both datasets. The receiver operating characteristic (ROC) analysis showed it had high sensitivity and specificity. Moreover, such a prognostic model also could be effectively applied to different subgroups, including groups of different ages, tumour sizes, histologic types, etc. A 5-DNA methylation signature identified by this study may act as a novel prognostic indicator for early-stage CC, and it may be helpful for the timely diagnosis and intervention of CC at pathological stages IA–IIA. Impact Statement: What is already known on this subject? Cervical cancer (CC) is one of the most common gynaecological malignant tumours. What the results of this study add? This study constructed a risk model based on a 5-DNA methylation signature for early-stage CC patients' survival prediction. What the implications are of these findings for clinical practice and/or further research? Methylated markers have the potential to discriminate patients of different risks and different OS. Our results may shed new light on the early diagnosis and intervention, and potential therapeutic targets for CC patients at pathological stages IA–IIA.